Four supervisory mentoring practices that support online doctoral students’ academic writing - Becker, Sandra; Jacobsen, Michele; Friesen, Sharon (Frontiers in Education, 2025)
Academic writing in both face-to-face and online environments is often fraught with tension, emotion, and challenge. The quality of doctoral students’ online academic writing experiences can be a difference maker in the successful completion of programs. This study examines how mentoring practices support online doctoral students’ academic writing, building on prior research that identified five enabling factors of effective online doctoral supervision, with a focus on cultivating a collaborative online community of support for academic writing. Using a comparative case study approach, interviews with five recently completed faculty of education doctoral graduates at a large university in western Canada were analyzed to identify four mentoring supervisory practices that support online doctoral students’ academic writing: (a) fostering a trusting, supportive community of practice; (b) engaging in regular synchronous meetings combined with iterative cycles of mentoring and scaffolding; (c) using coursework and program structures as a springboard for writing; and (d) providing diverse models of academic writing. Central to the effectiveness of the four online supervisory mentoring practices was the notion of trust which enabled students to develop their academic writing skills, scholarly identities, and successfully complete their doctoral degrees. This study is significant for identifying supervisory mentoring practices that led to students’ sense of gratitude and flourishing, further highlighting how crucial relational trust is for online doctoral students’ academic writing.